Panama: Agricultural R&D indicators factsheet - Stads, Gert-Jan; de los Santos, Luis (International Food Policy Research Institute, 2022)
Panama’s agricultural research spending has gradually increased during 2004–2020, at an average rate of 2.6 percent per year. Expenditure levels peaked in 2017, but they have remained relatively high since. The 2017 peak can to a large extent be explained by the construction and equipment of IDIAP’s new headquarters. Panama outperforms many of its Central American counterparts in a number of key agricultural R&D indicators. Compared to many of its neighbors, Panama invests a considerably higher proportion of its agricultural output in agricultural research; it employs a relatively high number of scientists with PhD degrees; and it generates an aboveaverage flow of research outputs in the form of publications, new crop varieties, and new agricultural technologies. A very large proportion of Panama’s PhD-qualified agricultural researchers is approaching retirement age, posing a significant problem for the future conduct and continuity of agricultural research. The country will need to recruit and train scientists without delay, and provide the necessary remuneration, working conditions, and incentives to maintain their commitment over time.